Coupled high-latitude climate feedbacks and their impact on atmospheric heat transport - Feldl N.; Bordoni S.; Merlis T. M. (Journal of Climate, 2017)
The response of atmospheric heat transport to anthropogenic warming is determined by the anomalous meridional energy gradient. Feedback analysis offers a characterization of that gradient and hence reveals how uncertainty in physical processes may translate into uncertainty in the circulation response. However, individual feedbacks do not act in isolation. Anomalies associated with one feedback may be compensated by another, as is the case for the positive water vapor and negative lapse rate feedbacks in the tropics. Here a set of idealized experiments are performed in an aquaplanet model to evaluate the coupling between the surface albedo feedback and other feedbacks, including the impact on atmospheric heat transport. In the tropics, the dynamical response manifests as changes in the intensity and structure of the overturning Hadley circulation. Only half of the range of Hadley cell weakening exhibited in these experiments is found to be attributable to imposed, systematic variations in the surface albedo feedback. Changes in extratropical clouds that accompany the albedo changes explain the remaining spread. The feedback-driven circulation changes are compensated by eddy energy flux changes, which reduce the overall spread among experiments. These findings have implications for the efficiency with which the climate system, including tropical circulation and the hydrological cycle, adjusts to high-latitude feedbacks over climate states that range from perennial or seasonal ice to ice-free conditions in the Arctic.